2020
DOI: 10.3390/ani10050819
|View full text |Cite
|
Sign up to set email alerts
|

Physiological State of Therapy Dogs during Animal-Assisted Activities in an Outpatient Setting

Abstract: Therapy dogs are increasingly being incorporated into numerous clinical settings. However, there are only a handful of studies that have focused on the impact of animal-assisted activity or therapy sessions on the wellbeing of the therapy dogs. Furthermore, these studies show mixed results. The goal of this study was to provide an in-depth picture of the effects of these interactions on the dogs involved by considering multiple physiological measures known to be associated with emotional state (continuous hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…Past literature has demonstrated that cortisol can increase due to exercise and general arousal (positive or negative) (13,15,23). It is recommended that future studies use cortisol and additional biomarkers, such as tympanic membrane temperature (36), heart rate variability (37), and salivary oxytocin (27,38). Furthermore, future studies would be beneficial in observing different therapy dog programs and their therapy teams' perceived stress along with the addition of objective physiological parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Past literature has demonstrated that cortisol can increase due to exercise and general arousal (positive or negative) (13,15,23). It is recommended that future studies use cortisol and additional biomarkers, such as tympanic membrane temperature (36), heart rate variability (37), and salivary oxytocin (27,38). Furthermore, future studies would be beneficial in observing different therapy dog programs and their therapy teams' perceived stress along with the addition of objective physiological parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Since the goal of AAI is aiding humans, studies on the topic have mainly focused on the effects that the animals have on the humans they are aiding. Only a few studies and publications have discussed the effect of AAI on animal welfare [ 13 , 14 , 15 , 16 ] and even fewer have studied animal welfare in AAI via experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…They did so primarily through a combination of behavioral assessment through structured observation and the analysis of cortisol samples. The use of heart rate and body temperature is, however, also seen [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Although it is disputed whether there is a relation between behavioral observations and cortisol measurements in dogs [ 23 , 24 , 25 , 26 , 27 ], both measures have individually been found to be indicative of animal welfare status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations